(untitled) (Spectrum Journal of Innovation, Reforms and Development, 2024)
In this article, we try to highlight the fact that many approaches that serve to ensure the mental, scientific, and cultural maturity of the youth of our nation are reflected in the spiritual heritage left by our jadid grandfathers, and today, education and education also enrich the content of love for the country in a unique way. The article analyzes the characteristics of jadidism, which occupied an important period in the development of our national education, and the ideas of humanity in it.